Kantian tradition in the Ethics of I.H.Abicht. - Tunaitis, Stepas (Problemos, 1974)
The seminar devoted to the 250th anniversary of I. Kant’s birth was held on the 17th of April 1974 in Vilnius University. Some of the addresses read at the seminar are published in this issue. S. Tunaitis traces back the Kantian tradition in the ethics of I. G. Abicht.